2011
DOI: 10.1155/2011/620849
|View full text |Cite
|
Sign up to set email alerts
|

Association of CD28 IVS3 +17T/C Polymorphism with Soluble CD28 in Rheumatoid Arthritis

Abstract: Objective: Rheumatoid arthritis (RA) is an autoimmune disease of unknown etiology in which inflammatory pathology involves T cell activation and the CD28 costimulatory molecule involved in T cell presentation. The gene includes the CD28 IVS3 +17T/C polymorphism that could be associated with susceptibility to RA whereas the soluble concentrations of CD28 (sCD28) could be related to clinical activity. Methods: We investigated the CD28 IVS3 +17T/C polymorphism in 200 RA patients and 200 healthy subjects (HS). Fur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 9 publications
(16 reference statements)
1
15
0
Order By: Relevance
“…Other important findings of this study were a trend of higher sCD28 levels in the RA patient groups compared with CS, and a significantly decrease in these levels in chronic RA patients compared with early RA patients. These findings are related to those previously reported in the study . High levels of sCD28 in RA patients could suggest a regulatory mechanism to compensate the activation in T cells.…”
Section: Discussionsupporting
confidence: 92%
“…Other important findings of this study were a trend of higher sCD28 levels in the RA patient groups compared with CS, and a significantly decrease in these levels in chronic RA patients compared with early RA patients. These findings are related to those previously reported in the study . High levels of sCD28 in RA patients could suggest a regulatory mechanism to compensate the activation in T cells.…”
Section: Discussionsupporting
confidence: 92%
“…In consequence it could influence immune homeostasis by disturbing balance between different isoforms of CD28 protein (Chen et al, 2012). In fact, the study performed by Ledezma-Lozano et al (Ledezma-Lozano et al, 2011) revealed that in group of rheumatoid arthritis patients, TC genotype in rs3116496T N C was associated with the decreased level of soluble CD28 form in comparison to TT. As far as rs6641T N G polymorphism is concerned, in the literature there is no data considering its function and association with MS susceptibility.…”
Section: Discussionmentioning
confidence: 99%
“…rs3116496, lead to the unbalanced expression of various CD28 protein isoforms by aberrant splicing, which leads to altered immune function. In line with this hypothesis, a report comparing sCD28 expression of each rs3116496 genotype in rheumatoid arthritis patients found higher sCD28 levels in TT carriers than in those with the TC genotype [21]. Further studies of the potential mechanisms underlying intronic polymorphisms, on CD28 pre-mRNA splicing, will therefore be interesting.…”
Section: Discussionmentioning
confidence: 78%
“…The relationship between the CD28 rs3116496 polymorphisms and susceptibility to various diseases, including cancer, has been previously investigated. Bechet’s disease [22], rheumatoid arthritis [21], and cervical cancer [23], [24], [25], [26], [27] are all known to be associated with the rs3116496 polymorphism. It was reported that the rs3116496 TT genotype was associated with a low risk of cervical cancer in a Chinese Han and in a Swedish population, respectively [23], [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation